Budaya Sunda dan Jejak Matematika : Menggali Kekayaan Etnomatematika di Kota Lumbung Padi - Fadillah, Sabina Nur; Rikayanti, (Prosiding Sesiomadika, 2024)
This research aims to explore the forms, activities, and contributions of mathematics to Sundanese culture in Balongsari Village, Rawamerta District, Karawang Regency. The research method used was descriptive qualitative with an ethnographic approach. The instruments used in this research are literature studies, documentation, and direct interviews with respondents. The data analysis technique was carried out using the method of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results showed that Sundanese culture typical of Balongsari Village has local wisdom related to mathematical concepts. Among them are the art of Jaipong Dance (the concept of floor patterns and movement patterns in dance, as well as mathematical activities on gamelan musical instruments); typical food, namely semprong (the concept of curved side space); traditional games including kaleci/kelereng (concepts of space, flat, and distance), panggal/gangsing (concepts of space, circle, and phytagoras theorem), kite pteng (concepts of flat, comparison, and congruence); and the Rawagede Monument (concepts of flat, space, and geometric transformation).